2023
DOI: 10.1002/wrna.1784
|View full text |Cite
|
Sign up to set email alerts
|

RNA epigenetic modifications in ovarian cancer: The changes, chances, and challenges

Abstract: Ovarian cancer (OC) is the most common female cancer worldwide. Patients with OC have high mortality because of its complex and poorly understood pathogenesis. RNA epigenetic modifications, such as m6A, m1A, and m5C, are closely associated with the occurrence and development of OC. RNA modifications can affect the stability of mRNA transcripts, nuclear export of RNAs, translation efficiency, and decoding accuracy. However, there are few overviews that summarize the link between m6A RNA modification and OC. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 175 publications
0
2
0
Order By: Relevance
“…Ovarian cancer is the fourth most common cancer of female worldwide [156]. Abundant of researches have showed that SULF1 is a known suppressor in ovarian cancers [157].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Ovarian cancer is the fourth most common cancer of female worldwide [156]. Abundant of researches have showed that SULF1 is a known suppressor in ovarian cancers [157].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Prevention and treatment of high-risk HPV cervical infections remain the main approach in combating CC, with the introduction of CC vaccines being a major development in recent years, together with screening technologies ( Rahangdale et al, 2022 ; Rimel et al, 2022 ; Sivars et al, 2022 ; Sun et al, 2022 ; Sabeena, 2023 ). OC, as the seventh most commonly diagnosed female cancer worldwide, poses as the fifth leading cause of cancer-related deaths in women and the most lethal of all gynecological malignancies ( Chen et al, 2023 ; Ye et al, 2023 ). Relatively few conventional screening tools exist for early detection, resulting in over 70% of the cases being diagnosed at advanced stages ( Armbrister et al, 2023 ; Brown et al, 2023 ; Terp et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%